Fasting Upregulates PPAR𝛼 Target Genes in Brain and Influences Pituitary Hormone Expression in a PPAR𝛼 Dependent Manner - Bettina König; Christine Rauer; Susann Rosenbaum; Corinna Brandsch; Klaus Eder; Gabriele I. Stangl (PPAR Research)
PPAR𝛼 is a lipid-activable transcription factor that mediates the adaptive response to fasting. Recent data indicate an important role of brain PPAR𝛼 in physiological functions. However, it has not yet been shown whether PPAR𝛼 in brain can be activated in the fasting state. Here we demonstrate that fasting of rats increased mRNA concentrations of typical PPAR𝛼 target genes implicated in 𝛽-oxidation of fatty acids (acyl-CoA oxidase, carnitine palmitoyltransferase-1, medium chain acyl-CoA dehydrogenase) and ketogenesis (mitochondrial 3-hydroxy-3-methylglutaryl-CoA synthase) in pituitary gland and partially also in frontal cortex and diencephalon compared to nonfasted animals. These data strongly indicate that fasting activates PPAR𝛼 in brain and pituitary gland. Furthermore, pituitary prolactin and luteinizing hormone-𝛽 mRNA concentrations were increased upon fasting in wild-type mice but not in mice lacking PPAR𝛼. For proopiomelanocortin and thyrotropin-𝛽, genotype-specific differences in pituitary mRNA concentrations were observed. Thus, PPAR𝛼 seems to be involved in transcriptional regulation of pituitary hormones.